A Framework for Developing Effective Technology-Enabled Distance Education Programs in Management: A Study of a Video Conference-Based Program in an Indian Perspective - Mukherje , Jaydeep; Mishra , Mukti (Journal of Law and Governance, 2007)
A major problem in delivering quality management education to working executives in India has been the inability of the candidates to leave their job for a prolonged period of time to attend the on-campus management programs. With the proliferation of two way Video Conferencing (VC) facilities across the country, as well as the use of Internet technology, this limitations could quite effectively be overcome for both students and management educators.